Does Expenditure Structure Affect Rural Poverty Alleviation in Indonesia? The Role of Village Fund Management - Agusta, Fian Ari; Khoirunurrofik, Khoirunurrofik (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2024)
This study aimed to explore public financial management at the village level and identify the types of village fund expenditures that had the most significant relationship in reducing short-term rural poverty in Indonesia. Using the 2019-2021 panel data and the fixed effect method, the authors analyzed the relationship between the five types of village fund spending on poverty in 49,192 village units. The estimation results showed that spending merely on village development negatively and significantly affected the number of low-income rural families in Indonesia. Meanwhile, spending on disaster management, emergencies, and village urgency indicated a positive and significant relationship with the number of low-income families in the village. It implies that the government should focus on spending programs and activities that create job opportunities and increase income for rural poverty reduction. The government also needs to improve data related to uniformity and validity in measuring, recording, and reporting data in ministries, institutions, and regional governments. Thus, in allocating village funds, the government must expand the formula allocation so that village funds can significantly reduce rural poverty.